Analisis Levelized Cost of Electricity (LCoE) pada PLTS Terapung dengan PLTS di Daratan: Study Kasus Pulau Kodingareng, Makassar Sulawesi Selatan - Radhiansyah Radhiansyah; Nur Azisah Syam; Muzakkir Muzakkir; Dwi Sahidin (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Indonesia, as an archipelagic country with over 17,000 islands, faces significant challenges in providing electricity access, particularly to small and remote islands. One promising solution is Solar Power Plants (PLTS), both land-based and floating solar plants that utilize water surfaces, suitable for areas with limited land availability. This study evaluates the economic feasibility of floating solar plants and land-based solar plants using the Levelized Cost of Electricity (LCoE) approach. LCoE encompasses all costs of construction, operation, maintenance, and energy production over the plant's lifespan, serving as a key benchmark in selecting power generation technologies. The findings show that the LCoE for floating solar plants is Rp11,197.00/kWh, lower than land-based solar plants at Rp11,769.00/kWh, although both exceed the electricity purchase price in Kodingareng, South Sulawesi, at Rp2,460.00/kWh. This difference is influenced by higher construction costs for floating solar plants but offset by greater energy output and lower operation and maintenance costs. This research provides a basis for developing solar power systems in archipelagic regions, emphasizing efficiency and sustainable energy solutions.